Arbuscular mycorrhizal growth responses are fungal specific but do not differ between soybean genotypes with different phosphate efficiency - Wang, Xiurong (Ann Bot, 2016)
Background and Aims Arbuscular mycorrhizal (AM) fungi play a key role in the phosphate (P) uptake of many important crop species, but the mechanisms that control their efficiency and their contribution to the P nutrition of the host plant are only poorly understood. Methods The P uptake and growth potential of two soybean genotypes that differ in their root architectural traits and P acquisition efficiency were studied after colonization with different AM fungi and the transcript levels of plant P transporters involved in the plant or mycorrhizal P uptake pathway were examined. Key Results The mycorrhizal growth responses of both soybean genotypes ranged from highly beneficial to detrimental, and were dependent on the P supply conditions, and the fungal species involved. Only the colonization with Rhizophagus irregularis increased the growth and P uptake of both soybean genotypes. The expression of GmPT4 was downregulated, while the mycorrhiza-inducible P transporter GmPT10 was upregulated by colonization with R. irregularis. Colonization with both fungi also led to higher transcript levels of the mycorrhiza-inducible P transporter GmPT9, but only in plants colonized with R. irregularis were the higher transcript levels correlated to a better P supply. Conclusions The results suggest that AM fungi can also significantly contribute to the P uptake and growth potential of genotypes with a higher P acquisition efficiency, but that mycorrhizal P benefits depend strongly on the P supply conditions and the fungal species involved.